HUBUNGAN PENGETAHUAN, SIKAP, PERILAKU DAN PERANSERTA DENGAN KESADARAN LINGKUNGAN HIDUP SERTA KESANGGUPAN MEMBAYAR MASYARAKAT SEKITAR BANTARAN SUNGAI DI KOTA PEKANBARU - Budi Darmawan; Zulfan Saam; Zulkarnaini Zulkarnaini (Jurnal Ilmu Lingkungan, 2010)
His research aim to detect the extent to which the relationship of these variables on a factorassociated with the variables on one or more other factors based on correlation coefficients. Thehypothesis proposed in this study were: (1) awareness of the environment is influenced by thevariable knowledge, attitudes, behavior and participation; (2) willingness to pay is influencedby the variable knowledge, attitudes, behaviors, and participation through environmentalawareness, and (3) willingness to pay is influenced by the ability to pay. Based on a hypothesistest results are not entirely acceptable, because the path coefficient based on testing a sub-structure, only the knowledge variable path coefficient (X1), behavior (X3) and participation (X4)on environmental awareness (Y) which is statistically meaningful and acceptable, whereas thepath coefficient attitude variable (X2) was not statistically significant and rejected. Secondhypothesis test results are not entirely acceptable, because the path coefficient based on testing,only the knowledge variable path coefficient (X1), behavior (X3) and participation (X4) againstthe capability to pay (Z) through environmental awareness (Y) and statistically significant andaccepted, whereas the path coefficient attitude variable (X2) was not statistically significant andrejected. While the relationship between the ability of the respondent's willingness to pay forriver water quality improvement program shows good relationship. This may illustrate that thehigher the ability to pay the respondents will follow the higher the willingness to pay.